(untitled) (Bangladesh Pharmaceutical Journal, 2020)
Plants are the priceless sources of bioactive natural compounds. Medicinal plants have been used since time immemorial in both developing and developed countries. Flemingia macrophylla (Willd.) is widely used as a hereditary medicines. The current study was designed to observe the analgesic, antidiarrheal and CNS depressant activities of methanol extract of the leaves of F. macrophylla (MEFM) and its petroleum ether (PEFM), dichloromethane (DFM), chloroform (CFM) and aqueous (AFM) fractions. The analgesic activities was assessed by acetic acid induced writhing method at doses 200- and 400- mg/kg body weight. The CNS-depressant effect was assayed by phenobarbitone sodium-induced sleeping time test. The anti-diarrheal activity of the extract was evaluated using castor oil-induced diarrhea in mice. The crude extract displayed significant peripheral analgesic activity at both test doses with 56.72- to 59.70-% inhibition of writhing responses, respectively. In CNS-depressant test, the extract revealed its activity in a dose dependent manner. In screening for antidiarrheal activity, the extract exhibited 20.83 and 41.67 % inhibition of defecation at 200- and 400-mg/kg bw, respectively whereas the standard loperamide (50 mg/kg bw) displayed 70.83 % inhibition of defecation. Bangladesh Pharmaceutical Journal 23(2): 141-145, 2020